UPLIFT OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イワタ, シュウジ; IWATA, Shuji (National Institute of Polar Research, 1993)
P(論文) The Sør Rondane Mountains, East Antarctica, originated from a marginal swell formed during the breakup of Gondwanaland, and the area is now in isostatic equilibrium. Altitude of the mountains is estimated to be controlled by the isostatic rebound associated with glacial denudation and ice loading. The denudational depth and extent of ice load subsidence were inferred from topographic cross sections of subglacial topography. The total mean erosion depth during 30Ma since the preglaciation was approximated 1.3km with an associated rebound of 1.1km. As a result of the uplift, the summit altitude in the preglacial time is estimated to have been 2.1km above the present sea level. The average rates of the denudation and surface uplift are 43m/Ma and 37m/Ma, respectively. departmental bulletin paper